Masculinities studies in Communication research in Brazil (Intercom - Brazilian Journal of Communication Sciences, 2022)
The purpose of this paper is to describe the development of research on masculinities in indexed Communication journals, based on an analysis of works published between 2000 and 2019 in Brazilian magazines indexed as A2 in Qualis 2013-2016. The studied parameters were: distribution by year, number of authors, affiliation, regional distribution, Communication interfaces, citation index, methodologies and theoretical framework. The results reveal an increase in the number of published research on masculinity in recent years and an articulation between the concepts of gender and the role of mass media, in a theoretical perspective that privileges resistance and visibility policies.
Keywords: Communication; Gender; Masculinities; Scientific production; Performativities